Stick em up! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The continued high prices for vanilla on the world market have led various countries to establish or revive vanilla production. Madagascar, the world s leading producer of vanilla (Vanilla fragrans), has not been able to contain the sky-rocketing...